Risk of adenoma recurrence after polypectomy in patients younger than 50 years vs. 50 years old and over with diminutive or small adenomas - Cai, Sicheng; Shi, Huiying; Fan, Mengke; Zhang, Qin; Lin, Rong (Frontiers in Oncology, 2022)
Background and aims Current studies have shown that polyp recurrence occurs after colonic adenomas polypectomy (AP), but the difference in recurrence risk between patients in patients older than 50 years and younger than 50 years has not been clearly studied. Methods 490 patients after AP were enrolled in the study. The patients were classified according to age (<50 years old or ≥50 years old), and then further categorized according to the baseline adenoma characteristics: Group 1: 1–2 non-advanced adenomas (NAAs) 1–5 mm in size; Group 2: ≥3 NAAs, 1–5 mm; Group 3: 1–2 NAAs, 6–9 mm; Group 4: ≥3 NAAs, 6–9 mm; and Group 5: advanced adenomas. Results During a mean follow-up interval of 2.52 years (2.51 years for ≥50 years old and 2.55 years for patients <50 years old), NAA recurrence was detected in 147 patients (30.0%). Overall, the hazard ratio (HR) for NAA recurrence after AP was higher in patients ≥50 years old than that in patients <50 years old (HR, 1.774, P = 0.003). For patients <50 years old, HRs (Group 2-5 vs. G1, respectively) for NAA recurrence were 0.744 (P = 0.773), 3.885 (P = 0.007), 5.337 (P = 0.003), and 3.334 (P = 0.015). For patients ≥50 years old, HRs (Group 2-5 vs. G1, respectively) for NAA recurrence were 1.033 (P = 0.965), 1.250 (P = 0.405), 2.252 (P = 0.015), and 1.887 (P = 0.009). For G1, the risk of NAA recurrence was significantly higher in patients ≥50 years old (HR, 2.932, P = 0.011) than that in patients <50 years old; for G2–G5, the risk was similar in the two age groups (P > 0.05). Conclusions For patients <50 years old with less than 3 NAAs that are 1–5 mm in size, the recurrence rate of NAA is less than that of patients ≥50 years old with the same index colonoscopy findings. When the adenomas are ≥5 mm, or their number exceeds 3, they have similar recurrence risk as that for patients ≥50 years old.